2012
DOI: 10.1186/1471-2229-12-198
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial ‘unintended effects’ of a cereal cystatin in transgenic lines of potato, Solanum tuberosum

Abstract: BackgroundStudies reported unintended pleiotropic effects for a number of pesticidal proteins ectopically expressed in transgenic crops, but the nature and significance of such effects in planta remain poorly understood. Here we assessed the effects of corn cystatin II (CCII), a potent inhibitor of C1A cysteine (Cys) proteases considered for insect and pathogen control, on the leaf proteome and pathogen resistance status of potato lines constitutively expressing this protein.ResultsThe leaf proteome of lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 66 publications
1
18
0
2
Order By: Relevance
“…2b). In agreement with studies reporting stress-related pleiotropic effects for recombinant cystatins in different plant species7 and the constitutive expression of naturally inducible pathogenesis-related (PR) proteins in potato lines expressing corn cystatin II43, ß-glucanases of the PR-2 family were up-regulated in leaves of cystatin-expressing clones compared to their steady-state levels in healthy leaves of parental line K (Fig. 2c).…”
Section: Resultssupporting
confidence: 91%
“…2b). In agreement with studies reporting stress-related pleiotropic effects for recombinant cystatins in different plant species7 and the constitutive expression of naturally inducible pathogenesis-related (PR) proteins in potato lines expressing corn cystatin II43, ß-glucanases of the PR-2 family were up-regulated in leaves of cystatin-expressing clones compared to their steady-state levels in healthy leaves of parental line K (Fig. 2c).…”
Section: Resultssupporting
confidence: 91%
“…Variations in the affinities of ectopically expressed protease inhibitors, such as OCI, for endogenous CPs may also explain previous observations of the absence of strong phenotypic effects arising from the ectopic expression of protease inhibitors in transformed plants (Badri et al ., ; Brunelle et al ., ; Masoud et al ., ; Rivard et al ., ), but not in others (Prins et al ., ; Van der Vyver et al ., ). Similarly, interspecific variations probably explain why the ectopic expression of other protease inhibitors, such as cereal cystatin in potato (Munger et al ., ) and a trypsin inhibitor in Nicotiana attenuate (Zavala et al ., ), produces large differences in effects on growth phenotype and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al (2005) have proposed that alterations in the fungal membrane permeability could be the origin of the antifungal properties of plant cystatins. Recently, it has been reported that plants overexpressing cystatin acquire increased abiotic stress tolerance as a result in an alteration of plant stress metabolism by upregulating several stress-related genes (Munger et al, 2012). Plants containing pYEH-scec were more resistant in the antimicrobial and insect feeding tests than either YEH-s or pYEH-ce, indicating that stacking the genes allowed plants to obtain the benefits of all three of the individual defence genes.…”
Section: Discussionmentioning
confidence: 99%
“…The single gene construct of chitinase was not employed and analysed in the present study, but is believed to be capable of enhancing both insect resistance and abiotic stress tolerance when used in the plastid system. It has been reported that plants overexpressing cystatin acquire increased abiotic stress tolerance as a result in an alteration of plant stress metabolism by upregulating several stress-related genes (Munger et al, 2012). Overexpression of chitinase in plants has also been shown to enhance tolerance to both biotic and abiotic stress (Ahmed et al, 2012;Nakamura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%